2022
DOI: 10.18421/tem112-16
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Intrinsic Motivation of Librarian Students using Virtual Reality for Education in the Context of Culture Heritage Museums

Abstract: In this study the effects of intrinsic motivation and learning competency of virtual realitybased learning is compared to traditional text-based learning. In the study 28 students were involved from the second and third years of the library and information science faculty. The application of the fully immersive virtual 3D environment of Wieng Yong House was developed to support the virtual realitybased learning in the context of museums for culture heritage. To verify the hypothesis, the control group (traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The N-gain number demonstrates that students' historical knowledge grew by 46% in the medium category after utilizing a museum that uses Virtual Field Trip technology as a history learning resource. The results of this study are consistent with those of other studies [6,15]- [18] that show how much simpler it is for students and teachers to learn historical events thanks to the accessibility of virtual museums. According to Yilmaz et al [19], virtual museums can be a useful learning tool for enhancing students' understanding of historical processes.…”
Section: Discussionsupporting
confidence: 91%
“…The N-gain number demonstrates that students' historical knowledge grew by 46% in the medium category after utilizing a museum that uses Virtual Field Trip technology as a history learning resource. The results of this study are consistent with those of other studies [6,15]- [18] that show how much simpler it is for students and teachers to learn historical events thanks to the accessibility of virtual museums. According to Yilmaz et al [19], virtual museums can be a useful learning tool for enhancing students' understanding of historical processes.…”
Section: Discussionsupporting
confidence: 91%
“…The analysis of pre-test and post-test results for knowledge acquisition showed significant improvements in both the non-gamified and gamified VR groups, as detailed in Table 5 and Figure 8; however, the gamified VR group did not show a significantly greater improvement in knowledge acquisition than the non-gamified VR group, contrary to expectations given the higher post-test scores observed. While direct comparisons in museum settings are scarce, related research in educational and training contexts suggests that gamification can improve learning outcomes compared to virtual reality alone [73][74][75]. Additionally, many studies have reported better knowledge retention with gamification [76][77][78], which could indicate the potential benefits of applying gamification in virtual reality within museum contexts.…”
Section: Rq3 Learning Outcomes From Implementing Gamification In Vrmentioning
confidence: 99%
“…Among the studies specifically dedicated to the evaluation of heritage learning in digital environments, some are concerned with gauging the effects of intrinsic motivation and competence obtained by means of virtual-reality-based learning, which are compared with traditional text-based learning [21]; it has also become possible to evaluate the potential of portals and other synchronous learning platforms to promote empathy among diverse cultural populations, considering that standard heritage spaces (for example, museums) should adopt synchronous learning to develop a more participatory and dynamic educational model [22]. Along this line, which seeks to combine face-to-face and virtual experience, the cognitive, emotional and social dimensions involved in the learning process have likewise become the object of analysis [23], and so have the processes linked to the transmission of heritage values on social media [24].…”
Section: Introductionmentioning
confidence: 99%